Comments on Jeske and Krueger's "Housing and the macroeconomy: The role of implicit guarantees for government sponsored enterprises" - Brian Peterson (Federal Reserve Bank of Atlanta, 2008)
This working paper comments on Karsten Jeske and Dirk Krueger's 'Housing and the Macroeconomy: The Role of Implicit Guarantees for Government Sponsored Enterprises', delivered at the Fiscal Policy and Monetary/Fiscal Policy Interactions conference held on April 19-20, 2007.
Keywords: 330; housing; mortgage market; default risk